Plasticity and evolution shape the scaling of metabolism and excretion along a geothermal temperature gradient - Benavente, Javiera; Fryxell, David; Kinnison, Michael; Palkovacs, Eric; Simon, Kevin (Dryad, 2022)
Physiological rates are heavily dependent on temperature and body size.
Most current predictions of organisms’ response to environmental warming
are based on the assumption that key physiological rates like metabolism
and excretion scale independently with body size and temperature and will
not evolve. However, temperature is a significant driver for phenotypic
variability in the allometric scaling and thermal sensitivity of
physiological rates within ectotherm species, suggesting that evolution
may play a role in shaping these parameters. We common-reared six
populations of western mosquitofish that have recently established (~100
years ago) in geothermal springs along a broad thermal gradient (19-33°C)
to determine whether these scaling parameters are affected by evolutionary
and/or plastic responses to warming over ecological timescales. Each
population was reared at four different temperatures (23, 26, 30 and
32°C). We measured routine metabolic and nitrogen excretion rates on
mosquitofish across a wide body size range. We found evidence for
plasticity, but not evolution, increasing the allometric scaling of
metabolic rate with temperature. Plasticity in metabolism allometry
reflected a decrease in thermal sensitivity at smaller body sizes. We
found evidence for evolution of phenotypic plasticity on the allometry of
excretion rate, reflecting evolutionary differences in how thermal
sensitivity varies with body size across different populations.
Evolutionary differences in excretion rate scaling did not influence the
relationship between excretion and metabolism across rearing temperatures,
suggesting that warming does not affect the balance between mosquitofish
energy demands and nutrient recycling rates.
Data metabolism, excretion and body size data were obtained from
introduced mosquitofish populations established in six geothermal springs
spanning a broad thermal gradient (19-33°C) t and reared at four different
temperatures (23, 26, 30 and 32°C). Routine metabolic rate was measured as
oxygen consumption (MO2) of individual fish for ten to fifteen minutes
inside closed-system respirometers. Nitrogen excretion rate was estimated
as change in ammonia (NH4+-N) concentrations in the closed respirometers
over the metabolism assays. Body size was measured as blotted wet weight.
There are missing values (NA) for routine metabolic rate in the
case of fish with highly fluctuating oxygen consumption traces
and NA for excretion rate in the case of issues analysing water
samples. Please see README file for key of column names.
Keywords: FOS: Natural sciences